Overcoming the odds: demonstrating aftercare model of providing targeted support to care experienced youth - Kiran Modi; Gurneet Kaur Kalra (Scottish Journal of Residential Child Care)
Aftercare is a vital continuum of care process, crucial for care experienced youths to fully realise their true potential and thereby become resilient members of society. In India, according to the Juvenile Justice (Care and Protection of Children) Act, 2015, institutional care should be seen as a ‘last resort’; yet there are large numbers of children living in childcare institutions (CCIs) due to the absence of robust family-based care models (Beyond 18, 2019). This paper highlights targeted interventions with CLs at various levels, through Aftercare Outreach Programmes (AOP), based on their needs assessment through a tool developed and implemented by Udayan Care. It presents the interventions applied in providing transition and rehabilitation support to Care Leavers (CLs) under several domains of the Sphere of Aftercare (Beyond 18). This support is provided holistically through skills: training and development – workshops, mentoring; education/vocational training: information, access, financial support; experience – internships, apprenticeships, placements; and bringing them together on a common platform, such as the care leavers network. As this programme, AOP, aims to mentor and guide these CLs through a smooth and supportive transition period, similar interventions during and post transition can be designed and applied to other CLs across the globe in different settings.